2021
DOI: 10.1016/j.neuron.2020.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Behavioral Components of Neocortical Signal Flow in Discrimination Tasks with Short-Term Memory

Abstract: In neocortex, each sensory modality engages distinct primary and secondary areas that route information further to association areas. Where signal flow may converge for maintaining information in short-term memory and how behavior may influence signal routing remain open questions. Using wide-field calcium imaging, we compared cortexwide neuronal activity in layer 2/3 for mice trained in auditory and whisker-based tactile discrimination tasks with delayed response. In both tasks, mice were either active or pas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 96 publications
7
55
0
Order By: Relevance
“…With the rapidly expanding efforts to link large-scale patterned cortical signals with sensory encoding, movement, and task performance 2,8,9,18,36,38 , several distinct strategies have been developed to analyze the spatiotemporal organization of network activity, including singular variable decomposition and non-negative matrix factorization 8,39 . Here, we show that functional parcellation of cortical regions 21 followed by diffusion embedding of time-varying correlations using a Riemannian geometry provides a robust means to quantify dynamic functional connectivity that accurately encodes fluctuations in behavior.…”
Section: Dynamic Functional Connectivity Suggests Distinct Cortical Subnetworkmentioning
confidence: 99%
“…With the rapidly expanding efforts to link large-scale patterned cortical signals with sensory encoding, movement, and task performance 2,8,9,18,36,38 , several distinct strategies have been developed to analyze the spatiotemporal organization of network activity, including singular variable decomposition and non-negative matrix factorization 8,39 . Here, we show that functional parcellation of cortical regions 21 followed by diffusion embedding of time-varying correlations using a Riemannian geometry provides a robust means to quantify dynamic functional connectivity that accurately encodes fluctuations in behavior.…”
Section: Dynamic Functional Connectivity Suggests Distinct Cortical Subnetworkmentioning
confidence: 99%
“…To isolate sensory activity, we used an encoding model and found clear responses in sensory, parietal and frontal cortex 40,41,57,58 . Consistent with our clustering results, these functional signals were unique for each PyN type and were either only partially represented in EMX mice or not observed at all.…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the multisensory nature of PPC and its functional modulation of V1 (Hishida et al, 2018 ). Recent studies demonstrated that PPC is involved in resolving sensory conflict during auditory-visual discrimination tasks (Song et al, 2017 ) and is involved in transferring sensory-specific signals to higher order association areas (Gallero-Salas et al, 2021 ). RL and AM, two HVAs, are considered part of the PPC because they display connectivity patterns similar to other components of the PPC (Gilissen et al, 2021 ).…”
Section: Cross-modal Recruitmentmentioning
confidence: 99%